2005
DOI: 10.1111/j.1440-1711.2005.01351.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered glycosylation of proteins produced by malignant cells, and application for the diagnosis and immunotherapy of tumours

Abstract: Summary Most secretory and membrane-bound proteins produced by mammalian cells contain covalently linked sugar chains. Alterations of the sugar chain structures of glycoproteins have been found to occur in various tumours. Because the sugar chains of glycoproteins are essential for the maintenance of the ordered social behaviour of differentiated cells in multicellular organisms, alterations to the sugar chains are the molecular basis of abnormal social behaviours in tumour cells, such as invasion into the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
178
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(183 citation statements)
references
References 59 publications
4
178
0
1
Order By: Relevance
“…18,19 Analyses of the Ost3p and its yeast paralogue Ost6p (human MagT1/IAP) demonstrated their function in regulating glycosylation efficiency 36 and recently also uncovered their oxidoreductase activity as well as a possible role in magnesium transport. 37 Aberrant glycosylation of proteins can be observed in essentially all in vitro cancer models and human cancers, and many glycosylated epitopes constitute tumor-associated antigens, 38,39 sustaining a long-standing debate regarding whether and how protein glycosylation is involved in tumorigenesis. Recently, global DNA methylation changes in ovarian cancer cells were linked to significant alterations of protein glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Analyses of the Ost3p and its yeast paralogue Ost6p (human MagT1/IAP) demonstrated their function in regulating glycosylation efficiency 36 and recently also uncovered their oxidoreductase activity as well as a possible role in magnesium transport. 37 Aberrant glycosylation of proteins can be observed in essentially all in vitro cancer models and human cancers, and many glycosylated epitopes constitute tumor-associated antigens, 38,39 sustaining a long-standing debate regarding whether and how protein glycosylation is involved in tumorigenesis. Recently, global DNA methylation changes in ovarian cancer cells were linked to significant alterations of protein glycosylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, alterations of the sugar chain of glycoproteins are associated with various diseases such as cancer (22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It is the most prevalent co-translational modification that occurs in the lumen of the ER. N-linked glycosylation plays an important role in maintaining protein stability, modulating protein-protein interactions, and protein membrane targeting (19)(20)(21).In addition, alterations of the sugar chain of glycoproteins are associated with various diseases such as cancer (22)(23)(24).In human GGCX, there are 9 potential N-linked glycosylation sequons. A study of the membrane topology of GGCX (25) demonstrated that all of the potential glycosylation sites are located in the ER lumen where the glycosylation enzymes occur.…”
mentioning
confidence: 99%
“…1,2 Glycosylation of proteins has been shown to change during malignant transformation; oligosaccharide expression is highly relevant to many diseases and the alteration of PTMs in proteins is one of the common features of cancer. 3,4 Among those, the most significant changes in carbohydrates have been described in terms of increased N-acetylglucosamine -1-6 branching in oligosaccharides, 5 inappropriate expression of polylactosamine extension, 6 or sialylation of the MUC1 mucin molecule resulting in the presence of truncated O-linked oligosaccharides chains accompanying breast cancer. 7,8 Aggressive cancers have also been reported to induce elevated levels of mono-and trisialylated oligosaccharides, found only in trace levels in nonaggressive cancers.…”
Section: Introductionmentioning
confidence: 99%